Acupuncture for premature ventricular complexes without ischemic or structural heart diseases: A systematic review and meta-analysis of clinical and pre-clinical evidence - Cai, Yiyi; Zhang, Claire Shuiqing; Liu, Shaonan; Zhou, Li; Tang, Boyan; Chen, Wensheng (Frontiers in Medicine, 2022)
Background With increasing evidence suggesting potential benefits, acupuncture is often applied to the treatment of premature ventricular complexes (PVCs), particularly in symptomatic patients who fail or are unsuitable for medications or refuse catheter ablation. However, the existing clinical evidence is inconsistent. Objectives This review aims to systematically evaluate the effectiveness and safety of acupuncture therapies for PVCs without ischemic or structural heart diseases, when it is compared with sham/placebo acupuncture or usual care, or used as an add-on therapy to routine care; and to summarize existing pre-clinical research evidence supporting the effects of acupuncture therapies for this clinical condition. Methods Four English-language databases, four Chinese-language databases and seven clinical registries were searched from their inceptions to May 21, 2021 and updated to November 01, 2022. Trials comparing acupuncture with sham acupuncture or evaluating the add-on effects of acupuncture were included. Primary outcomes are the number of premature ventricular beats (PVBs) and effective rate defined as “the proportion of participants with over 50% decrease in the number of PVBs from baseline to the end of treatment measured by 24-h Holter”. Results A total of 479 records were identified with nine trials involving 847 participants included in this review. Meta-analysis on two sham-control trials with low risk of bias for all domains suggested that acupuncture could significantly reduce the number of PVBs (RR 3.83, 95% CI [2.19, 6.7], I2 = 0%). Moreover, the combination of acupuncture and standard treatment was superior to standard treatment alone in reducing the burden of PVBs (RR 1.21, 95% CI [1.08, 1.36], I2 = 0%). Though no treatment protocol consensus was announced, body acupuncture on point PC6, HT7, DU10, DU11, and ST36 with duration of needle retention ranging from 15 to 30 min for a 4-week treatment period is broadly used by the included trials. For experimental evidence, five studies explored the mechanisms of acupuncture for PVCs were eventually included into analysis and PC6 was the most frequently studied acupuncture point. Moreover, a reduction of electrical activity of sympathetic nerves in experimental animals undergoing electro-acupuncture was observed by four of these studies. Conclusion Sham-controlled RCT evidence with moderate-level certainty suggested that acupuncture could be a therapeutic option to reduce the burden of PVBs in patients without ischemic or structural heart diseases. Further clinical studies using validated and reliable outcome measurement instruments and bench research to unveil the mechanisms of acupuncture stimulation and point-specific effects for PVCs are needed. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=262132], identifier [CRD42021262132].